The Role of Non-Genomic Information in Maintaining Thermodynamic Stability in Living Systems - Robert A. Gatenby; B. Roy Frieden (Mathematical Biosciences and Engineering)
Living systems represent a local exception, albeittransient, to the second law of thermodynamics, which requiresentropy or disorder to increase with time. Cells maintain a stableordered state by generating a steep transmembrane entropy gradientin an open thermodynamic system far from equilibrium through avariety of entropy exchange mechanisms. Information storage in DNAand translation of that information into proteins is central tomaintenance thermodynamic stability, through increased order thatresults from synthesis of specific macromolecules from monomericprecursors while heat and other reaction products are exportedinto the environment. While the genome is the most obvious andwell-defined source of cellular information, it is not necessarilyclear that it is the only cellular information system. In fact,information theory demonstrates that any cellular structuredescribed by a nonrandom density distribution function may storeand transmit information. Thus, lipids and polysaccharides, whichare both highly structured and non-randomly distributed increasecellular order and potentially contain abundant information aswell as polynucleotides and polypeptides. Interestingly, there isno known mechanism that allows information stored in the genome todetermine the highly regulated structure and distribution oflipids and polysacchariedes in the cellular membrane suggestingthese macromolecules may store and transmit information notcontained in the genome. Furthermore, transmembrane gradients ofH$^+$, Na$^+$, K$^+$, Ca$^+$, and Cl$^-$ concentrationsand the consequent transmembrane electrical potential representsignificant displacements from randomness and, therefore, richpotential sources of information.Thus, information theory suggeststhe genome-protein system may be only one component of a largerensemble of cellular structures encoding and transmitting thenecessary information to maintain living structures in anisoentropic steady state.